If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X/3=(2+X)/4
We move all terms to the left:
X/3-((2+X)/4)=0
We add all the numbers together, and all the variables
X/3-((X+2)/4)=0
We calculate fractions
4X^2/()+(-((X+2)*3)/()=0
We calculate terms in parentheses: +(-((X+2)*3)/(), so:We get rid of parentheses
-((X+2)*3)/(
We multiply all the terms by the denominator
-((X+2)*3)
We calculate terms in parentheses: -((X+2)*3), so:We get rid of parentheses
(X+2)*3
We multiply parentheses
3X+6
Back to the equation:
-(3X+6)
-3X-6
Back to the equation:
+(-3X-6)
4X^2/()-3X-6=0
We multiply all the terms by the denominator
4X^2-3X*()-6*()=0
We add all the numbers together, and all the variables
4X^2-3X*()=0
| 2y+3=21-4y | | 2x-5+(8/x)=0 | | 2x+6=7x14 | | 6x8=x | | -2x²+5x-3=0 | | 3^3x+2=243 | | 5-2=-5x/2 | | 2-(3x-7/4)+x+17/5=0 | | 21–x=4x. | | 1-2x/5=2-x/2 | | 4D^4+4D^3-3D^2-2D+1)y=0 | | -27/x+0.5x+1.5=0 | | x2+15x-56.25=0 | | x2-7x-34=10 | | 11m-6m=30 | | 10x-6x2=0 | | 2x-7=3x-20 | | x²-4x+5=0 | | 10x-6x=0 | | 4x+10x=0 | | x/4+1/4=-3/4x-5/6 | | 3/4x-2=5-1/4x | | -2/7+x=5/7 | | 12x-8=20-x | | x+1/2=3/2 | | 3-2a=5a+10 | | 5/x+5=2 | | 3x-2/x+2=2 | | 4/5=24/x+5 | | (3x+50)/8=4 | | 2/x=3/x-6 | | 3/4x+2/x=2+1/2x |